Estudio de la influencia que tiene la molienda mecánica a altas energías en la morfología y la formación de fases en polvos de hueso de cerdo con el propósito de obtener hidroxiapatita sin fases espurias (2021)
Hydroxyapatite (HA) (Ca10 (PO4) 6 (OH) 2 is a bioceramic intended for the development of bone substitutes, due to its presence in the inorganic phase of bone and dental tissues. However, the production of synthetic HA involves procedures costly and complex, likewise, due to the absence of trace elements (NA, Mg and Al), commercial HA does not show metabolic activity. On the other hand, animal bones are also considered as an alternative source for obtaining HA crystals, which possibly promote cell growth. The objective of this project is to study the influence of the experimental parameters of grinding (speed and turning time), in the morphological characteristics and the formation of crystalline phases during the obtaining of HA powders from pig bone. The material to be subjected to the grinding process was obtained from the crushing of femoral bone previously subjected to a deproteinization process, and the mechanical grinding. as of this material was made in a single-arm planetary mill. Two experimental series were established, in the first three rotation speeds were established for 2 hours and in the second several times of grinding at 650 rpm were analyzed. The samples obtained were characterized by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM), from the analysis of results it was possible to determine the conditions that allow obtaining the appropriate characteristics to continue with the process of obtaining crystalline hydroxyapatite with the smallest possible particle size.